The spider does not always win the fight for attention: Disengagement from threat is modulated by goal set - Vromen, J.; Lipp, Ottmar; Remington, R. (Routledge, 2014)
Stimulus-driven preferential attention to threat can be modulated by goal-driven attention. However, it remains unclear how this goal-driven modulation affects specific attentional components implied in threat interference. We hypothesise that goal-driven modulation most strongly impacts delayed disengagement from threat. A spatial cueing task was used that disentangles delayed disengagement from attentional capture by tightly manipulating the locus of attention at the time of target onset. Different top-down goals were induced by instructing participants to identify bird/fish targets (Experiment 1) or spider/cat targets (Experiment 2) among animal non-targets. Delayed disengagement from a non-target spider was observed only when the spider was part of the target set, not when it was task-irrelevant. This corroborates evidence that threat stimuli do not necessarily override goal-driven attentional control and that extended processing of threatening distractors is not obligatory.